Kajian Studi Literatur : Pelatihan Untuk Pengembangan Karyawan UMKM - Saifur Rijal, Muhammad; Sopiah, Sopiah (Dinasti Review Publisher, 2023)
The purpose of this research is to conduct a systematic review of literature related to employee development in SMEs and to provide a deeper understanding of employee development in SMEs and identify best practices that can help employee development in SMEs. The method used in this research is a systematic literature review. Data were taken from online databases such as Google Scholar, ScienceDirect, and ProQuest. The keywords used in the search were